2018
DOI: 10.1002/adfm.201807760
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance, Transparent Thin Film Hydrogen Gas Sensor Using 2D Electron Gas at Interface of Oxide Thin Film Heterostructure Grown by Atomic Layer Deposition

Abstract: A high-performance, transparent, and extremely thin (<15 nm) hydrogen (H 2 ) gas sensor is developed using 2D electron gas (2DEG) at the interface of an Al 2 O 3 /TiO 2 thin film heterostructure grown by atomic layer deposition (ALD), without using an epitaxial layer or a single crystalline substrate. Palladium nanoparticles (≈2 nm in thickness) are used on the surface of the Al 2 O 3 /TiO 2 thin film heterostructure to detect H 2 . This extremely thin gas sensor can be fabricated on general substrates such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 54 publications
1
28
0
1
Order By: Relevance
“…目前, ALD技术已在 微电子领域得到了广泛应用, 包括用于制备微处理器 中的晶体管栅介电层 [ 5 ] 、集成电路中的互连籽晶 层 [5] 、动态随机存储器(DRAM)和3D NAND器件结 构中的介电层等 [6,7] . 同时, ALD技术也被广泛应用于 微纳机电系统 [5,8] 、显示与发光 [5,9,10] 、光伏 [11~13] 、能 源存储 [14~18] 、催化与电催化 [19~23] 、传感器 [24,25] 、表 面防腐 [5,26,27] 、太空防护 [28] 以及药物缓释 [29] ; ALD沉积薄 膜的厚度由周期数精确控制, 因此可从原子尺度精确 控制薄膜的厚度; ALD生长温度一般较低(室温至 400℃), 可用于在温度敏感的基底材料(如有机材料) 上沉积薄膜 [24] ; ALD沉积薄膜的重复性好, 适用于大 面积薄膜的制备.…”
Section: 控制薄膜的厚度和成分 可在复杂三维结构上沉积均unclassified
“…目前, ALD技术已在 微电子领域得到了广泛应用, 包括用于制备微处理器 中的晶体管栅介电层 [ 5 ] 、集成电路中的互连籽晶 层 [5] 、动态随机存储器(DRAM)和3D NAND器件结 构中的介电层等 [6,7] . 同时, ALD技术也被广泛应用于 微纳机电系统 [5,8] 、显示与发光 [5,9,10] 、光伏 [11~13] 、能 源存储 [14~18] 、催化与电催化 [19~23] 、传感器 [24,25] 、表 面防腐 [5,26,27] 、太空防护 [28] 以及药物缓释 [29] ; ALD沉积薄 膜的厚度由周期数精确控制, 因此可从原子尺度精确 控制薄膜的厚度; ALD生长温度一般较低(室温至 400℃), 可用于在温度敏感的基底材料(如有机材料) 上沉积薄膜 [24] ; ALD沉积薄膜的重复性好, 适用于大 面积薄膜的制备.…”
Section: 控制薄膜的厚度和成分 可在复杂三维结构上沉积均unclassified
“…Later work has demonstrated that 2DEGs can be formed at more simple interfaces, between amorphous and single-crystalline oxides [30,31] with the benefit of room temperature preparation. Recently 2DEGs were shown to form even at amorphous/polycrystalline oxide interfaces [17,21,32,33] (Figure 1C). Furthermore, the oxide deposition temperatures were reduced from 650-900 °C to 25-300 °C, and the deposition techniques have been extended from PLD to the more scalable atomic layer deposition (ALD), which is widely used by the microelectronics industry.…”
Section: Introductionmentioning
confidence: 99%
“…These oxide interfaces provided a fertile ground for the discovery and manipulation of extraordinary physics, such as superconductivity [2][3][4][5], magnetism [6,7], magnetoelectric coupling [8,9], Rashba spinorbit coupling [10], persistent photoconductivity [11,12], and integer/fractional quantum Hall effect [13,14]. Over the last decade, leveraging these phenomena towards various devices, such as transistors [15][16][17][18][19], diodes [20], gas sensors [21], spintronic devices [22,23], and memory devices [24][25][26][27][28][29], has drawn considerable attention. In addition to the exotic phenomena listed above, the emergence of a high sheet density of electrons (typically 10 12 ∼10 15 cm −2 ) between two insulators is already attractive for some devices, such as in the role of channels or back electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Therefore, it is essential to monitor the leakage of hydrogen at trace levels. [3][4][5] SnO 2 is one of the most reported n-type semiconducting metal oxide (SMOX) employed in chemo-resistive gas-sensing, due to its wide band gap (3.6 eV at 300 K), low material cost, fast response, stability and simplicity. [6][7] However, SnO 2 -based gas sensors are limited by their low selectivity, e.g.…”
Section: Introductionmentioning
confidence: 99%